2012
DOI: 10.1002/bdrb.21008
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Toxicity Study of Lersivirine in Mice

Abstract: Lersivirine is a second-generation nonnucleoside reverse transcriptase inhibitor undergoing clinical development for the treatment of HIV-1. An embryo-fetal developmental toxicity study was performed to evaluate the maternal and developmental toxicity of lersivirine in pregnant mice. Mated Crl:CD1(ICR) mice were administered 0, 150, 350, and 500 mg/kg lersivirine once daily by oral gavage on gestation days 6 to 17, followed by cesarean section on gestation day 18. The first 2 days of dosing for the high-dose g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…2), demonstrate that lersivirine is not teratogenic in rabbits. In addition, lersivirine was not teratogenic in mice (Cappon et al, in press). The results of the lersivirine developmental toxicity studies, in concert with the apparent lack of signal for teratogenesis with other first generation NNRTIs such as delavirdine and nevirapine, supports a conclusion that the teratogenic signal attributed to efavirenz is specific to that compound and does not represent an NNRTI class effect, a term which should be used very carefully.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2), demonstrate that lersivirine is not teratogenic in rabbits. In addition, lersivirine was not teratogenic in mice (Cappon et al, in press). The results of the lersivirine developmental toxicity studies, in concert with the apparent lack of signal for teratogenesis with other first generation NNRTIs such as delavirdine and nevirapine, supports a conclusion that the teratogenic signal attributed to efavirenz is specific to that compound and does not represent an NNRTI class effect, a term which should be used very carefully.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for lersivirine to cause developmental toxicity and teratogenicity was evaluated in standard embryo‐fetal development (EFD) studies in mice and rabbits in which lersivirine was administered daily throughout the major period of organogenesis. The EFD study performed in pregnant mice revealed no evidence of teratogenicity (Cappon et al, in press). The EFD study in rabbits showed no teratogenic effects of lersivirine in the mid and low dose, but yielded equivocal findings for axial skeletal malformations at the high dose, which could not be dismissed as potentially related to treatment without additional information.…”
Section: Introductionmentioning
confidence: 99%
“…For example, nephrogenesis in humans is completed in utero, whereas in mice and rats it occurs postnatally (Table 1) (Cappon and Hurtt, 2010). Thus, for certain drugs that act on a specific organ, studies that include only in utero exposures in mice and rats, but not postnatal administration, may not capture all the effects that could potentially occur in humans.…”
Section: Mammalian Pregnancy and Embryofetal Developmentmentioning
confidence: 99%